PERBEDAAN KETERAMPILAN PERTOLONGAN PERSALINAN NORMAL ANTARA MEDIA MODEL DAN MEDIA VIDEO PADA MAHASISWA SEMESTER TIGA DI PRODI DIII KEBIDANAN STIKES MUHAMMADIYAH LAMONGAN TAHUN 2016 - Kustini Kustini (Universitas Islam Lamongan, 2018)
Lack of midwives, knowledge and skills leads to low performance and quality of service. The effort can be done is increase the knowledge and skill, reality shows that most learning using only one kind of media and one time demonstration. The issue is using media is minimize exactly on practical helping labor and laboratories learning in STIKES Muhamadiyah Lamongan.The purpose of this study is to determine the difference skill helping normally labor using model and Video in STIKES Muhammadiyah Lamongan 2016. This research is comparative analytical study with cross sectional approach. The population is 100 students and the sample of 80 student, uses simple random sampling. Independent variable is the use of model and video, dependent variable is skill of helping normally labor.The results is more than a majority respondent who use model is able to doing skill helping normally labor, that 29 respondent (72,5%), and more than majority proficient doing skill helping normally labor, that 24 respondent (60%).Analysis using SPP 16.0 with Mann Whitney test α = 0,05, p=0.000 so p < α, concluded that there are difference skill helping normally labor between using model and video media.Seeing these results it is necessary to use a medium that is thought to correspond to the learning objectives that lead to learning motivation so that skills become better destination.Keywords: media, models, videos, normal delivery